2021
DOI: 10.1007/s40121-021-00489-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality and Drug Resistance Among Carbapenem-Resistant Enterobacteriaceae-Infected Pancreatic Necrosis Patients

Abstract: Introduction: Carbapenem-resistant Enterobacteriaceae (CRE) has emerged as a global threat to hospitalization patients. Infected pancreatic necrosis (IPN) leads to high risks of CRE infections with increasing mortality. Our study aims to determine the predictors related to 90-day overall mortality of CRE IPN. Methods: We retrospectively reviewed the drug resistance rates and clinical characteristics of CRE IPN patients from January 1, 2016, to January 1, 2021. Independent predictors of mortality were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
6
8
1
Order By: Relevance
“…For the first time, our study suggests that the timing of first intervention should focus on lactic acid during the pre-intervention phase. In line with a previous study, our findings confirmed that procalcitonin plays a key role in the evaluation of infections, which alerts us to timely clearance of the source of infection [ 5 , 27 ]. For CRO-infected CAP patients, clinicians also need to consider the efficacy of the infectious source control which, although difficult to assess, may influence the duration of antibiotic therapy [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For the first time, our study suggests that the timing of first intervention should focus on lactic acid during the pre-intervention phase. In line with a previous study, our findings confirmed that procalcitonin plays a key role in the evaluation of infections, which alerts us to timely clearance of the source of infection [ 5 , 27 ]. For CRO-infected CAP patients, clinicians also need to consider the efficacy of the infectious source control which, although difficult to assess, may influence the duration of antibiotic therapy [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…Carbapenems were previously considered the last-line choice for multidrug-resistant Gram-negative bacterial infections [ 3 , 5 , 23 ]. With the overuse of antibiotics in recent years, CRO have become an important pathogen of nosocomial infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…K. pneumoniae , as the second most common nosocomial gram-negative bacterium, leads to significantly high all-cause mortality in worldwide [ 10 , 12 , 14 , 25 ]. Carbapenem, amikacin and tigecycline used to be effective and latest antibiotics for MDR- K. pneumoniae treatments, but recent researches revealed that drug-resistance rates of these three antibiotics were significantly increasing which may be associated with overuse during treatments [ 24 , 26 ]. In this era of MDR bacterial infections, clinician in all departments should pay more attentions on the preventions and treatments of MDR- K. pneumoniae infections [ 13 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…To further verify this conclusion, we matched the predictors in the multivariate logistic regression model except BUN, and continuous variables including ALB and procalcitonin were stratified by the median cut-off point. In addition, confounders that reportedly affect outcomes for AP or SAP, including age, APACHE II score, and mMarshall score, were matched [5][6][7][8][9][10][11] (Table 5). After PSM, BUN levels were still higher in the mortality group than in the survival group (18.415 [IQR,19.555] mmol/L vs. 10.63 [IQR, 6.03] mmol/L; P = 0:005).…”
mentioning
confidence: 99%